2005
DOI: 10.1111/j.1365-2214.2005.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Mum knows best? Psychological status in an oncology sample

Abstract: Both mothers and fathers are perceptive to their child's psychological status, and it is therefore satisfactory to consider their opinions about their children. Children in the age range 11-16 years are able to express their views with as much accuracy as parents irrespective of their gender and diagnosis and so should be included in assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Despite significant rank correlations between fathers and mothers on these scales, fathers reported significantly higher scores than mothers for hyperactivity, conduct problems and total difficulties suggesting that fathers are more sensitive to externalising behaviours than are mothers, or that they over-report in this domain. In a study of psychological status of a sample of 11-16 year old children with cancer, [35] fathers also reported higher SDQ scores than mothers for hyperactivity, conduct problems, and total difficulties. Furthermore, paternal ratings of conduct problems were very similar to children's self-ratings, whereas mothers' ratings were lower.…”
Section: Analysis Of Continuous Sdq Subscale Scoresmentioning
confidence: 89%
See 1 more Smart Citation
“…Despite significant rank correlations between fathers and mothers on these scales, fathers reported significantly higher scores than mothers for hyperactivity, conduct problems and total difficulties suggesting that fathers are more sensitive to externalising behaviours than are mothers, or that they over-report in this domain. In a study of psychological status of a sample of 11-16 year old children with cancer, [35] fathers also reported higher SDQ scores than mothers for hyperactivity, conduct problems, and total difficulties. Furthermore, paternal ratings of conduct problems were very similar to children's self-ratings, whereas mothers' ratings were lower.…”
Section: Analysis Of Continuous Sdq Subscale Scoresmentioning
confidence: 89%
“…Furthermore, paternal ratings of conduct problems were very similar to children's self-ratings, whereas mothers' ratings were lower. A possible explanation is that since mothers are more often the primary caregivers and spend more time with their children than fathers [36] they become desensitised to their children's problem behaviour [35]. Although our analysis did not show a significant difference in mother and father correlations between mothers who stayed at home to look after the family and mothers who did not, we were limited by a small sample size.…”
Section: Analysis Of Continuous Sdq Subscale Scoresmentioning
confidence: 94%
“…Fathers were as " in tune " with their children as mothers of children with chronic disease (23,29) . However, two articles noted that medical personnel speak primarily to females ahead of males, which further enhanced the father ' s sense of isolation (16,22) .…”
Section: Resultsmentioning
confidence: 99%
“…Even though our objective was to limit our search to fathers of adolescents, we finally enlarged it to include younger children because, if only using studies including participants aged 10 years or older, we would have found only five articles (8,17,23,34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…The Strengths and Difficulties Questionnaire (SDQ) (described in further detail below) is a brief, free, validated, and easy-to-administer tool commonly used to screen for child/adolescent psychological well-being and behavior (Goodman, 1997). Although previous studies have utilized the SDQ with pediatric oncology populations (Bruce, Rodgers, Firth, & Freeston, 2005;Upton & Eiser, 2006), there is no evidence pertaining to how this measure performs in this illness context.…”
Section: Introductionmentioning
confidence: 99%